2019
DOI: 10.1002/jsfa.9983
|View full text |Cite
|
Sign up to set email alerts
|

A new analytical method to measure S‐methyl‐l‐methionine in grape juice reveals the influence of yeast on dimethyl sulfide production during fermentation

Abstract: BACKGROUND Dimethyl sulfide (DMS) is a small sulfur‐containing impact odorant, imparting distinctive positive and / or negative characters to food and beverages. In white wine, the presence of DMS at perception threshold is considered to be a fault, contributing strong odors reminiscent of asparagus, cooked cabbage, and creamed corn. The source of DMS in wine has long been associated with S‐methyl‐l‐methionine (SMM), a derivative of the amino acid methionine, which is thought to break down into DMS through che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…No significant change of DMS throughout the storage period was apparent but DMSO gradually decreased (P < 0.05) (Table 1). The decrease of dimethyl sulfoxide could be due to the reductase activity of the microbial population transforming dimethyl sulfoxide into dimethyl sulphide, which was previously found in the fermentation process of various wines and beers (Silva Ferreira et al, 2003, Deed et al, 2019, Bamforth, 2014Szlavko & Anderson, 1979).…”
Section: Resultsmentioning
confidence: 71%
“…No significant change of DMS throughout the storage period was apparent but DMSO gradually decreased (P < 0.05) (Table 1). The decrease of dimethyl sulfoxide could be due to the reductase activity of the microbial population transforming dimethyl sulfoxide into dimethyl sulphide, which was previously found in the fermentation process of various wines and beers (Silva Ferreira et al, 2003, Deed et al, 2019, Bamforth, 2014Szlavko & Anderson, 1979).…”
Section: Resultsmentioning
confidence: 71%
“…This molecule is known to accumulate during ageing via the degradation of its main precursor (i.e. S ‐methylmethionine), 33 whereas a recent study has shown that, even though marginal, yeast and fermentation conditions can also play an effect in the production of dimethyl sulfide in wine 34 . Here, average levels of DMS were quantified at 37.6 ± 19.1 μg L −1 , which displays both the high presence of this molecule, as well as its fluctuation between samples.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that dimethyl sulfide has an impact on blackcurrant aromas through perceptual interactions in low concentrations (Escudero et al, 2007;Lytra et al, 2014). However, the dimethyl sulfide formed during alcoholic fermentation (therefore by yeasts (Deed et al, 2019)) is mainly eliminated because this molecule is very volatile. Its concentration after 1.5 years is around 10µg/L (Segurel et al, 2004) and has an impact on blackcurrant aromas.…”
Section: Impact Of Pre-fermentation Treatmentmentioning
confidence: 99%